Association of thyroid disorders in patient with Diabetes mellitus, hospital based, single centric cross sectional study - Adhikari, Krishna Raj; Poudel, Rajendra; Poudel, Srijana; Sigdel, Sujita (Journal of Advances in Internal Medicine, 2025)
BACKGROUND Diabetes and thyroid dysfunctions are globally increasing common health problem. Both of these problems are metabolically related to each other. Early screening of thyroid disorders in diabetic patient helps in diagnosis and identification of the disease and its complication for better management. Hyperthyroidism and thyrotoxicosis can worsen Diabetes mellitus and cause hyperglycemia and poor Blood sugar control. So we have conducted this study to find the association of Diabetes mellitus and Thyroid disorders in our part of the country.METHODS It was a hospital based descriptive cross sectional study which was conducted among 180 patients in Pokhara academy of health sciences Pokhara from Nov 2023 to October 2024.Ethical clearance was taken from Institutional review committee. Diabetic patients were evaluated for thyroid dysfunction. Demographic profile, Diabetic status and thyroid function test was carried out. Results were analyzed using SPSS 21 version.RESULTS A total of 180 patients enrolled in the study 41.1% (n=74) were male, while 58.9% (n=106) were female. Thyroid stimulating Hormone (TSH) levels have a weak but statistically significant positive correlation with diabetes parameters, (FBS: r=0.223, p=0.003) (PPBS: r=0.168, p=0.024) (HbA1c: r=0.218, p=0.003), implying that higher TSH levels indicative of hypothyroid was associated with poorer glucose control.CONCLUSION Thyroid disorders are more commonly associated with diabetes mellitus. Early screening of thyroid disorder in Diabetic is beneficial for the patient.